Systematization of crimes against the order of military service in the legislation of the Republic of Uzbekistan - Yusupov Nodirbek Akramovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the general situation with the classification of the norms of responsibility for crimes against the order of military service, reflects current scientific proposals on the norms requiring additional classification, and provides feedback on theoretical and practical effectiveness.